The other side of the innate immune system: humoral arms favoring cancer - De Santis, Maria (Cell Mol Immunol, 2020)
Cancer cells take advantage of NETosis to escape host immune surveillance and mediate metastasis. The pharmacological targeting of NETosis may prove beneficial in maximizing the response to cancer immunotherapy.